Aspirations and income, food security and subjective well-being in rural Ethiopia - Daniel Ayalew Mekonnen; Nicolas Gerber (University of Bonn, Center for Development Research (ZEF), 2016)
Despite some improvements in recent years, poverty and food insecurity remain widespread and the main challenges in Ethiopia. Using individual and household level data collected in rural Ethiopia, we examine if aspirations are strongly associated with well-being outcomes, as posited in the aspirations failure framework articulated by Ray (2006) and others. We employ both bivariate and multivariate analyses. We find that aspirations (particularly that of the household head) are indeed strongly associated with the household per-capita income and expenditure and with various triangulating measures of household food (in)security including per-capita calorie consumption, the food consumption score (FCS), the household dietary diversity score (HDDS), and the household food insecurity access scale (HFIAS). Contrary to a few other studies, we also find strong evidence that, in rural Ethiopia, aspirations are positively associated with satisfaction in life and/or happiness. Findings in this study provide suggestive evidence that policies aimed at improving well-being outcomes might benefit from multiple effects (both direct and indirect) if they incorporate aspirations raising strategies.
Keywords: D03; I31; O12; 330; aspirations; income; poverty; food security; subjective well-being; Ethiopia